Impact of Electronic Human Resource Management Practices on Employees' Job Satisfaction in the Banking Sector - Rawat, Shankar Kumar; KC, Sudarshan (Journal of Emerging Management Studies, 2024)
Purpose - The study aims to examine the impact of electronic human resources management (e-HRM) practices focusing e-recruitment, e-selection, e-compensation, e-learning and Training, e-performance appraisal, and e-communication on employees' satisfaction in Kathmandu based commercial banks. Design/methodology/approach - Structure questionnaires were used to collect data from 401 respondents who were working in the commercial banks in Kathmandu district. Data were analyzed using SPSS version 25. A multiple regression analysis was conducted to predict the employees' satisfaction from all six independent variables i.e., e-recruitment, e-selection, e-compensation, e-learning and Training, e-performance appraisal, and e-communication. Findings and Conclusion - The findings indicate that employee satisfaction and e-HRM practices are positively correlated. The banking industry can benefit from the implementation of e-HRM systems by encouraging employee achievement, which in turn leads to increased job satisfaction. E-HRM facilitates to achieve strategic corporate goals by satisfying employees. Implications - E-HRM practices create conducive work environment where employees develop positive attitude towards the organization. High job satisfaction among bank employees enhances their productivity, organizational citizenship behavior and organizational commitment. It also decreases absenteeism, employee turnover and job related stress level. Hence, a high-performing e-HRM system may be useful for commercial banks to maintain harmony between employees' personal goals and organizational goals.